2020
DOI: 10.1021/acs.accounts.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Multilayer Electrodes: From the Basics to Energy Applications

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Growing environmental concern has increased the demand for clean energy, and various technologies have been developed to utilize renewable energy sources. With the development of highly efficient energy conversion and storage systems, fundamental studies on the electrochemistry of electrodes are critical because the functionality of most of these systems relies on interfacial electrochemical reactions that occur on the surfaces of the electrodes. In this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Previous research has also shown that increasing the number of layers increases the active surface area and active sites, so does the electrochemical behavior. 63 EIS is a reliable technique that is employed to investigate the charge-transfer mechanisms associated with the varying layer constructions. EIS was employed to measure the conductive properties of the PEI/[(TBA)Mo 12 (AleThio) 4 ] bilayers in 0.5 M H 2 SO 4 .…”
Section: Electrocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Previous research has also shown that increasing the number of layers increases the active surface area and active sites, so does the electrochemical behavior. 63 EIS is a reliable technique that is employed to investigate the charge-transfer mechanisms associated with the varying layer constructions. EIS was employed to measure the conductive properties of the PEI/[(TBA)Mo 12 (AleThio) 4 ] bilayers in 0.5 M H 2 SO 4 .…”
Section: Electrocatalytic Hydrogen Evolution Reactionmentioning
confidence: 99%
“…The LbL process is a prevalent cyclic process that alternately deposits functional thin films of multiple materials onto various substrates with nanometer precision. 17 The LbL electrode offers many benefits: (ⅰ) providing hybrid thin films with a regular order, (ⅱ) balancing the requirements between improved mass loading and insufficient conductivity of thick electrodes without dead volume (Figure 3), [30][31][32][33] (ⅲ) exhibiting good compatibility with most deposition techniques, and (ⅳ) lowering the charge transfer resistance to enhance the rate capability. 18 Additionally, electrodes based on the LbL design show much popularity in the field of electronic miniaturization due to enormous advantages of thin-film technology, including the ease of material synthesis/deposition, the well-developed fabrication (such as patterning and lithography), and integration technique in the semiconductor field.…”
Section: Lbl-assembled Electrode Design For Mscsmentioning
confidence: 99%
“…For the latter, composite electrodes with either sandwichlike or double-decker architectures were successfully fabricated and exhibited similar stable cycling performance at a high curtailing capacity (4 mAh cm –2 ). Such designed architectures may enable further mechanistic investigations into Li–O 2 electrocatalytic chemistry in thick electrodes …”
Section: Applications Of Dry-pressed Holey Graphene Electrodesmentioning
confidence: 99%
“…Such designed architectures may enable further mechanistic investigations into Li−O 2 electrocatalytic chemistry in thick electrodes. 48 Soluble catalysts, or redox mediators (RMs), were also explored with the high-mass-loading hG air cathode platform. 36 Unlike heterogeneous electrocatalysts which are typically metalcontaining compounds, the RMs are small ions or molecules that are soluble in the electrolyte and thus much more effective in accessing the insoluble discharge products to improve the charge reaction.…”
Section: Neat and Composite Air Cathodes And Architectures For Li−o 2...mentioning
confidence: 99%